2017
DOI: 10.15640/jhrmls.v5n1a1
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Environmental Attitude of Employee in the Relationship between Environmental Training and Environmental Orientation of Organization

Abstract: This paper aims to examine the relationships among environmental training, environmental attitude of employee and environmental orientation of organization and the mediating effect of environmental attitude of employee in the relationship between environmental training and environmental orientation of organization. In order to achieve the study objectives, primary data were collected from 108 employees of selected leading apparel company which is operating in Batticaloa and Polonnnaruwa areas of Sri Lanka. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
3
0
0
Order By: Relevance
“…This agrees with the results of (Sang et al, 2018), which indicated that that China is at a very early stage of green practices in construction field. This is due to the need for taking care of creating successful green performance by project managers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with the results of (Sang et al, 2018), which indicated that that China is at a very early stage of green practices in construction field. This is due to the need for taking care of creating successful green performance by project managers.…”
Section: Discussionsupporting
confidence: 92%
“…This consistency appears due to the agreement between studies in literature on the positive relationship between HR green competencies and organizational environmental performance, so any progressive change in environmental performance requires change in employees' green competencies. Also this study agrees with the study of (Salem, Hasnan, & Osman, 2012) which approved that green competencies positively affect organizational environmental performance . However this disagrees with the results of (Salem et al, 2012) which indicated that there is insignificant relationship between organizational competencies and environmental performance.…”
Section: Hypotheses Testingsupporting
confidence: 92%
See 1 more Smart Citation